Stegnografi Menggunakan Metode Least Significant Bit dan Quick Response Code (QR-Code) - Ispandi Ispandi; Ahmad Fauzi; Sugiono Sugiono (STMIK Budi Darma, 2019)
Transmission of information through the internet can involve sensitive personal data that can be tapped, there are many applications and websites that require good security to avoid the safety of theft of documents and confidential information. Stegnography is the art and science of writing stored secret messages that are not separate from the sending and the recipient is asked related to hidden messages, images as one of the many digital media that can be used as objects to insert messages or secret messages using methods Least Significant Bit (LBS) This method determines data by replacing the bits of data that at least means that it is closed with bits of confidential data. From this meode the author will combine with the Quick Response Code (QR), in order to produce encryption that has higher security, the result of embedding the cover image into a stgno image, will be encrypted again to Quick Response Code (QR).